(untitled) (Sinología hispánica. China Studies Review, 2021)
This article analyzes the connections between China’s foreign policy guidelines and traditional Chinese strategic thinking, where Confucian and Taoist conceptions provide guidelines for understanding the world views discussed in schools of international relations. The measures adopted by the Chinese authorities based on Chinese philosophical thought are also analyzed and linked in order to verify that their application is still valid and that the strategies and tactics that General Sunzi indicates in his book The Art of War or the teachings Taoist master Zhuangzi remain a practical guide for Chinese leaders in their geostrategic movements, understandable to the people and useful for maintaining harmony and unity.